Concise Review: Fabrication, Customization, and Application of Cell Mimicking Microparticles in Stem Cell Science. (9th January 2018) - Labriola, Nicholas R.; Azagury, Aharon; Gutierrez, Robert; Mathiowitz, Edith; Darling, Eric M.
Abstract : Stem and non-stem cell behavior is heavily influenced by the surrounding microenvironment, which includes other cells, matrix, and potentially biomaterials. Researchers have been successful in developing scaffolds and encapsulation techniques to provide stem cells with mechanical, topographical, and chemical cues to selectively direct them toward a desired differentiation pathway. However, most of these systems fail to present truly physiological replications of the in vivo microenvironments that stem cells are typically exposed to in tissues. Thus, cell mimicking microparticles (CMMPs) have been developed to more accurately recapitulate the properties of surrounding cells while still offering ways to tailor what stimuli are presented. This nascent field holds the promise of reducing, or even eliminating, the need for live cells in select, regenerative medicine therapies, and diagnostic applications. Recent, CMMP-based studies show great promise for the technology, yet only reproduce a small subset of cellular characteristics from among those possible: size, morphology, topography, mechanical properties, surface molecules, and tailored chemical release to name the most prominent. This Review summarizes the strengths, weaknesses, and ideal applications of micro/nanoparticle fabrication and customization methods relevant to cell mimicking and provides an outlook on the future of this technology. Moving forward, researchers should seek to combine multiple techniques to yield CMMPs that replicate as many cellular characteristics as possible, with an emphasis on those that most strongly influence the desired therapeutic effects. The level of flexibility in customizing CMMP properties allows them to substitute for cells in a variety of regenerative medicine, drug delivery, and diagnostic systems.